THE INFLUENCE OF LIFESTYLE ON PURCHASING DECISION OF â€œGUESSâ€ BRANDED GOODS IN MANADO - Rahajeng, Adetea Pavita; Massie, James D.D; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Lifestyle describes a person as a whole that interacts with the environment. Currently, the role of branded goods to be bought in Indonesia has become a daily habit. Guess brand products are known as products that have an image as an outfit with a new design, color and good quality and give a prestigious impression that fits with the lifestyle of Indonesian people, especially the city of Manado so people do not hesitate to spend a lot of money to buy it. The aim of this study is to know and analyze the lifestyle affect the purchase decision and how the activity, interest and opinion variable influence purchase decision of Guess branded goods in Manado. This research is a causal type of research through questionnaires and uses multiple regression analysis. 100 respondents are the sample size of this research. The result shows that the independent variable which are activity, interest and opinion have simultaneously influence on Purchase Decision as a dependent variable. Activity variable shows that does not have significant influence on purchase decision. Interest variable shows that does have significant influence on purchase decision. And opinion shows that does have significant influence on purchase decision of Guess Branded Goods in Manado.Â Keywords: lifestyle, AIO, purchase decision, â€œGuessâ€ branded goods